Resource-Based View Theory to Achieve a Sustainable Competitive Advantage of the Firm: Systematic Literature Review - Mailani, Desi; Hulu, Margareth Zhandra Trixie; Simamora, Mikhael Radot; Kesuma, Sambas Ade (International Journal of Entrepreneurship and Sustainability Studies, 2024)
The Resource-Based View (RBV) Theory  explains the importance of VRIN/O resources and characteristics for achieving the sustainable competitive advantage. The purpose of this SLR is to analyze the role of RBV in the process of achieving SCA, especially in the supply chain and customer information field, as well as the role of RBV in previous research and for independent startup companies. This Systematic Literature Review (SLR) was created based on previous research that was collected and analyzed to obtain facts that support the current research findings. Data collection was carried out using the literature review method by classifying and eliminating data sources that did not meet certain indices, which then resulted in the finding that the RBV Theory plays a role in the supply chain in forming SCA by creating VRIN/O resources, namely maintaining good relationships with suppliers and then deploying and using resources. power properly. In addition, customer information can be a resource in VRIN/O, which is expected to increase and maintain customer loyalty, which is part of a sustainable competitive advantage. Based on previous research, RBV is not suitable for application in operations management research and startups. However, it encourages entrepreneurs to be more creative in managing their limited resources. Efforts have been made to write and collect facts in this SLR as much as possible, but like research in general, this SLR cannot be free from the limitations of dependence on actualization of previously collected data sources.